Removal of Emergent Pollutants by a Vertical Flow Constructed Wetland with Vetiveria Zizanioides: A Case Study for Caffeine - Almeida, Adelaide; Oliveira, Júlio; Matias, Flávia; Ribeiro, Carlos; Silveira, Daniele; Tavares, Jorge (KnE Materials Science, 2022)
This work evaluated caffeine removal in a vertical flow constructed wetland (VFCW), planted with Vetiveria zizanioides. The feeding was continuous (synthetic influent: mineral medium and caffeine) to reduce the concentration variations in the bed. Two influent concentrations (0.75 ± 1.0 mg·L−1 and 1.5 ± 1.0 mg·L−1) were used with a constant hydraulic load (100 ± 10 L·m−2·d−1). Plant growth was monitored weekly, and characterization was carried out to determine the levels of chlorophyll a and b, pigments and carotenoids, and nutrients (nitrogen, phosphorus, magnesium, calcium, sodium and potassium). HPLC-MS was used to determine the caffeine concentration. The caffeine removal efficiency reached averages of 93 ± 1% and 87 ± 1% (retention time: 6.23 ± 0.23 hours). The caffeine contents in the influent did not affect chlorophyll a, total chlorophyll or carotenoids, and an increasing trend throughout the tests was observed. Sodium and potassium contents also showed an increase with higher caffeine concentration. This preliminary study showed that removing caffeine from wastewater using a VFCW is promising. Keywords: wastewater, emergent pollutants, caffeine, vertical flow constructed wetlands, Vetiveria zizanioides